2002
DOI: 10.1074/jbc.m206088200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Isolated Human Phosphodiesterase-5 Regulatory Domain Induces an Apparent Conformational Change and Increases cGMP Binding Affinity

Abstract: The superfamily of cyclic nucleotide phosphodiesterases (PDEs) 1 is comprised of eleven known families of PDEs that vary in substrate specificity, regulatory properties, and tissue distribution (1, 2). The regulatory domains of five of the known PDE families (PDEs 2, 5, 6, 10, and 11) contain either one or two sequences known as GAF domains, and these are homologous among the five families. In three of these families (PDEs 2, 5, and 6), at least one of these sequences in each monomer forms an allosteric site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
84
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 22 publications
2
84
1
Order By: Relevance
“…Those fast k on and k off values for hPDE5 GAF-cyaB1 AC are at variance with results for cGMP binding to PDE5, where on and off kinetics were about 15 min for the on-reaction (11) and up to 7 h for the off-reaction (10,24). Similarly, binding assays with the isolated PDE5 GAF domains have demonstrated that cGMP binding and release are slow (15,17,18,24). We examined cGMP binding to hPDE5 GAF-cyaB1 AC chimera following standard protocols (10, 27).…”
Section: Biochemical Characterization Of Hpde5 Gaf-cyab1 Ac-mentioning
confidence: 72%
See 3 more Smart Citations
“…Those fast k on and k off values for hPDE5 GAF-cyaB1 AC are at variance with results for cGMP binding to PDE5, where on and off kinetics were about 15 min for the on-reaction (11) and up to 7 h for the off-reaction (10,24). Similarly, binding assays with the isolated PDE5 GAF domains have demonstrated that cGMP binding and release are slow (15,17,18,24). We examined cGMP binding to hPDE5 GAF-cyaB1 AC chimera following standard protocols (10, 27).…”
Section: Biochemical Characterization Of Hpde5 Gaf-cyab1 Ac-mentioning
confidence: 72%
“…Effect of the N Terminus on PDE 5 GAF-cyaB1 AC ActivationUsing various PDE5 GAF domain constructs, cGMP binding constants between 0.027 and 1.9 M have been reported in the past (15,17,18,22,24,27). Possibly different N-and C-terminal truncations have contributed.…”
Section: Biochemical Characterization Of Hpde5 Gaf-cyab1 Ac-mentioning
confidence: 99%
See 2 more Smart Citations
“…20,35,36 The g subunit of PDE6 also acts as a substrate for phosphorylation at several distinct sites within the central region of this 10 kDa protein. Phosphorylation of g at Thr (22) or Thr (35) has little effect on the PDE6 holoenzyme itself, but greatly diminishes the ability of activated transducin to bind the g subunit and relieve inhibition of catalysis. 37 Phosphorylation of g at Thr(62) in nonretinal tissue has been reported to regulate mitogenic signaling via interactions with proteins other than PDE6 catalytic subunits (whose expression is confined to the retina and pineal gland).…”
Section: S30mentioning
confidence: 99%